The TSC Complex-mTORC1 Axis: From Lysosomes to Stress Granules and Back - Rehbein, Ulrike; Prentzell, Mirja Tamara; Cadena Sandoval, Marti; Heberle, Alexander Martin; Henske, Elizabeth P.; Opitz, Christiane A.; Thedieck, Kathrin (Frontiers in Cell and Developmental Biology, 2021)
The tuberous sclerosis protein complex (TSC complex) is a key integrator of metabolic signals and cellular stress. In response to nutrient shortage and stresses, the TSC complex inhibits the mechanistic target of rapamycin complex 1 (mTORC1) at the lysosomes. mTORC1 is also inhibited by stress granules (SGs), RNA-protein assemblies that dissociate mTORC1. The mechanisms of lysosomal and SG recruitment of mTORC1 are well studied. In contrast, molecular details on lysosomal recruitment of the TSC complex have emerged only recently. The TSC subunit TSC1 binds lysosomes via phosphatidylinositol 3,5-bisphosphate (PI(3,5)P2). The SG assembly factors 1 and 2 (G3BP1/2) have an unexpected lysosomal function in recruiting TSC2 when SGs are absent. In addition, high density lipoprotein binding protein (HDLBP, also named Vigilin) recruits TSC2 to SGs under stress. In this mini-review, we integrate the molecular mechanisms of lysosomal and SG recruitment of the TSC complex. We discuss their interplay in the context of cell proliferation and migration in cancer and in the clinical manifestations of tuberous sclerosis complex disease (TSC) and lymphangioleiomyomatosis (LAM).